Construction stability analysis of intersection tunnel in city under CRD method - Ren, Yiwei; Zhou, Shijun; Jia, Jiayin; Yuan, Qiang; Zhou, Zelin; Liu, Maoyi; He, Huayong (Frontiers in Earth Science, 2023)
The construction of city intersection tunnels cause multiple redistribution of surrounding rock stress, resulting in the engineering disasters such as instability in existing tunnels and collapses of ground buildings. To mitigate formation disturbances effectively, the Center Cross Diagram (CRD) method is employed in city tunnel construction. In this study, a numerical model for a city intersection tunnel is developed based on an underground circular roads project in Chongqing, China, to analyze the safety of the tunnel structure and the stability of ground buildings under the CRD method. The numerical simulation results obtain that the excavation of pilot-tunnel ➃ will reduce the surrounding rock stress and control the rock strata subsidence, and reveal that the excavation of pilot-tunnel ➃ is the key step of CRD method. The maximum compressive stress and tensile stress of surrounding rock first increase and then decrease during the excavation of pilot-tunnels ➀, ➁, ➂, and ➃. Simultaneously, the deformation of the ground building experiences a slow initial increase followed by a rapid rise before stabilizing. Furthermore, the excavation of the main tunnel leads to an increase of 0.73, 0.35, and 0.52 times in the vault subsidence value, left haunch convergence value, and right haunch convergence value of branch tunnel #1, respectively. Finally, the convergence process of branch tunnel #1 is discussed through the in-situ monitoring, which is divided into three stages: rapid deformation, deceleration deformation, and stable deformation. The final horizontal convergence value and subsidence value of cross-section K0+360 are respectively 84% and 78% of those at cross-section K0+395.